Predatory publishing – A cautionary for researchers - Kanchan , Tanuj (Journal of Indian Academy of Forensic Medicine, 2019)
Predatory publishing usually refers to publication of  substandard journals or books etc. with the sole motive of  minting money from, or at the cost of unsuspecting researchers.  Thus, the idea of predatory publishing is to seek financial gains,  and there are hardly any academic interests involved. The  outcome is very obvious; release of journals and books with  poor scientific content. The significant contrast between  predatory and non-predatory publishing is based on the level of  editorial and publishing efforts taken to check the quality of the  content. It takes a lot of serious efforts on the part of the editorial  and publishing team to ensure that quality articles with reliable  and useful information only are passed on in the academic  circles. It has been emphasized time and again to make  researchers aware of the problems associated with predatory
Keywords: publishing; cautionary; researchers